Association between Ear Fullness, Earache, and Temporomandibular Joint Disorders in the Elderly - Macedo, Julya; Doi, Marcelo; Oltramari-Navarro, Paula Vanessa; Gorres, Vanessa; Mendes, Marina Stephany; Silva, Izabele Machado; Navarro, Ricardo; Marchiori, Luciana Lozza (International Archives of Otorhinolaryngology, 2014)
Introduction An earache (otalgia or ear pain) is pain in one or both ears that may last a short or long time. Earache is prevalent in the population with temporomandibular joint disorders (TMJDs), but there is a dearth of epidemiologic studies regarding the association between TMJD and ear pain and ear fullness in older people.Objective To assess the presence of earache and ear fullness in elderly patients with TMJD.Methods A cross-sectional study was conducted in independently living, elderly individuals. TMJD was assessed by dental evaluation and earache was verified by medical history. Statistical analysis was performed using the chi-square test and relative risk.Results Of the 197 subjects evaluated in this part of the study, 22 had earache, and 35 was verified by ear fullness. Of the 22 subjects with earache, none had conductive or mixed hearing loss in the ears tested. There was a significant association (p = 0.036) between the TMJD and earache (odds ratio = 2.3), but there was no significant association between the TMJD and ear fullness.Conclusion These results highlight the importance of identifying risk factors for earache that can be modified through specific interventions, which is essential in the prevention of future episodes, as well as managing the process of treatment of elderly patients in general.
Keywords: earache; elderly; temporomandibular joint disorders